Reflection of Feminism in Veronica Roth's Divergent - L. Dyah P. Wardani, Dianita Prasetyo Ningrum (Universitas Muhammadiyah Jember, 2017)
Abstract Reflection of feminism is seen through the statements, ideas, and behaviors in Divergent novel. It is depicted through its major female characters. Those characters show their power, strength, and bravery which are different with women in common. In this research, I use the theory of literature by Rene Wellek and Austin Warren which is used to analyze the characterization through the major female characters in the novel which are constructed by Veronica Roth. Then, feminism by Simone de Beauvoir is applied to know how the social status of those major female characters is and how they have reflected feminism. Finally, this analysis will show to the readers about women's power. The analysis of the reflection of feminism in Divergent novel shows women also have the same rights as men, and women are not always subjugated. According to statements, behaviors, and ideas of feminism in the novel, it is shown that every woman actually can choose whatever they want depending on their own desire. Keywords: reflection, feminism, women's power, equal rights.